Coalitional ZP-Equilibrium in games and its existence - Nessah, Rabia; Larbani, Moussa; Tazdait, Tarik (2015)
In this paper, we introduce the coalitional ZP-equilibrium with undetermined parameters. This equilibrium is individual rational for each coalition for the subgame when the rest of players play their strategy equilibrium, it presents the global behavior of the players in each coalition and it admits the collective behavior of players against the uncertainty. We show that under some conditions on quasiconcavity of the utility payoffs, is enough to guarantee the existence of coalitional ZP-equilibrium in compact, convex and continuous normal form games with undetermined parameters.